The Effectiveness of Internship Programs in Empowering Job Seekers in Ngawi Regency, East Java - Isna Husnul Mar’ati Ardiana; Hendrawati Hamid (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2026)
The Unemployment Rate in Ngawi Regency remains relatively high compared to other regions in East Java, due to low workforce readiness and limited access to job information. To address this, the Ngawi Regency Trade, Industry, and Manpower Office implemented an internship program for job seekers at PT Dwi Prima Sentosa. This study, titled “Effectiveness of Internship Programs in Empowering Job Seekers in Ngawi Regency, East Java,” aims to examine and describe the program’s effectiveness in empowering job seekers and increasing labor absorption. A qualitative descriptive method was used, with data collected through semi-structured interviews using purposive sampling, supported by observation and documentation. The results indicate that the internship program is effective. Planning and implementation by stakeholders align with initial objectives, and the outputs and outcomes meet the expectations of both the government and participants. The program successfully empowers job seekers and improves employment absorption, suggesting its potential to reduce the Open Unemployment Rate in Ngawi Regency in the future.